(untitled) (Research, Society and Development, 2023)
Breastfeeding is a practice of exclusive breastfeeding, which raises several discussions for a global strategy to improve maternal and child health. Therefore, the objective: to understand the actions carried out by nurses to promote exclusive breastfeeding. Methodology: This is a research with characteristics of an integrative literature review, of a descriptive nature based on studies carried out in the area of nursing, where the aim is to qualitatively analyze articles. Results and Discussions: The research results were constructed through an analysis of theoretical surveys Initial 240; excluded by titles163; excluded due to duplicity 57, excluded due to not being in one of the descriptors 03. Selected 17 publications and 03 books on Scientific Methodology. Final Considerations: It was found that the actions of the health professional, the nurse, begin with adherence to Pre-Natal, and this professional is part of the health care line, guiding, providing support and support, as well as monitoring to mothers in the first hours of their baby’s life. It is suggested that this article will be a point of reference for nursing academics, health professionals who work with EBF, as well as other professionals, using this source of scientific research to improve the phenomenon researched, referencing each author who contributed to make this research tangible.